One-pot fabrication of CdxZn1-xS/ZnO nanohybrid using mixed sulfur sources for photocatalysis. (May 2020) - Qiu, Jianhao; Li, Ming; Wan, Yiling; Zhang, Shu; Wang, Huanting; Yao, Jianfeng
Graphical abstract: Highlights: Cdx Zn1-x S/ZnO nanocomposites were readily fabricated via a facile one-pot method. The Cd/Zn molar ratios were tuned by altering the amounts of Na2 S and Na2 S2 O3 . Cdx Zn1-x S/ZnO showed glorious performance on photocatalytic reduction of Cr(VI). Cd0.68 Zn0.32 S/ZnO nanoparticles have tiny diameters of about 5−8 nm. Abstract: Cdx Zn1-x S/ZnO nanohybrids were fabricated by using mixed Na2 S and Na2 S2 O3 as the sulfur source via a facile one-pot synthesis. Cdx Zn1-x S/ZnO with x = 0.54, 0.58, 0.62, 0.68 and 0.75 was successfully tuned by altering the molar ratio of Na2 S and Na2 S2 O3 . Sole sulfur source Na2 S or Na2 S2 O3 could only generate Cd0.5 Zn0.5 S or CdS/ZnO, respectively. The in-situ co-growth of Cdx Zn1-x S and ZnO makes them combine penetratingly in Cdx Zn1-x S/ZnO nanohybrids, giving them a highly intimate contact. The natural matched band-edge positions and highly intimate contacts between Cdx Zn1-x S and ZnO are conductive to charge separation and transfer. Benefiting from the structural and compositional merits, the optimized Cdx Zn1-x S/ZnO nanohybrid with sizes of about 5−8 nm exhibited outstanding performance for Cr(VI) reduction under visible-light illumination. The newly designed one-pot synthetic strategy in this work may provide a brand-new pathway in developing high-efficiency multi-component photocatalysts for practical use.